2021
DOI: 10.1111/jdv.17290
|View full text |Cite
|
Sign up to set email alerts
|

Adverse skin reactions related to PPE among healthcare workers managing COVID‐19

Abstract: Hands 244 (49.8%) Chin 40 (8.1%) Neck 22 (4.4%) Trunk 02 (0.4%) Axilla 01 (0.2%) Groin 05 (1%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Two more articles were identified via relevant citations from some of the full‐text articles. After assessing full‐length articles, 20 studies were excluded for the following reasons: did not provide usable statistics 8–10 ( n = 3), characterized the dermatoses poorly or did not specify the location of dermatoses 11–24 ( n = 14), only included patients presenting to dermatological clinic already with mask‐related dermatoses 25 ( n = 1), all patients had pre‐existing facial dermatoses 26,27 ( n = 2). After these exclusions, 37 published studies were included in the meta‐analysis 28–64 …”
Section: Resultsmentioning
confidence: 99%
“…Two more articles were identified via relevant citations from some of the full‐text articles. After assessing full‐length articles, 20 studies were excluded for the following reasons: did not provide usable statistics 8–10 ( n = 3), characterized the dermatoses poorly or did not specify the location of dermatoses 11–24 ( n = 14), only included patients presenting to dermatological clinic already with mask‐related dermatoses 25 ( n = 1), all patients had pre‐existing facial dermatoses 26,27 ( n = 2). After these exclusions, 37 published studies were included in the meta‐analysis 28–64 …”
Section: Resultsmentioning
confidence: 99%
“…Stratum corneum breakdown reduced the overall tolerance to mechanical loading and caused adverse skin reactions in 70-97% of HCWs. [9][10][11] Several studies have reported adverse skin reactions to hand hygiene and PPE, including erythema, papules, urticaria, dry skin, scales, maceration, and itching. The most commonly affected site was the nose, hand, and cheeks.…”
Section: Introductionmentioning
confidence: 99%